2020
DOI: 10.1016/j.jcrc.2020.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive therapy with vitamin c and thiamine in patients treated with steroids for refractory septic shock: A propensity matched before-after, case-control study

Abstract: Triple therapy with steroids, vitamin C and thiamine has been recently proposed as a safe and beneficial in patients with sepsis. In 2017, we added the use of intravenous vitamin C and thiamine in septic shock patients receiving low dose hydrocortisone because poorly responsive to vasopressors. Aim of this study is to verify whether triple therapy rather than steroids alone can improve outcome in patients with refractory shock. Materials and methods: In this before-after retrospective analysis, we compared sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…The studies by Marik et al (2017), Litwak et al (2019) and Iglesias et al (2020) all displayed a reduction in renal replacement therapy for sepsis patients who received HAT therapy compared to the control group, who only received standard care. In contrast, the other studies showed no significant difference in the requirement of renal replacement therapy between the treatment group and the control group (Coloretti et al, 2020; Fujii et al, 2020; Hwang et al, 2020; Moskowitz et al, 2020; Sevransky et al, 2020; Vail et al, 2020).…”
Section: Resultsmentioning
confidence: 92%
“…The studies by Marik et al (2017), Litwak et al (2019) and Iglesias et al (2020) all displayed a reduction in renal replacement therapy for sepsis patients who received HAT therapy compared to the control group, who only received standard care. In contrast, the other studies showed no significant difference in the requirement of renal replacement therapy between the treatment group and the control group (Coloretti et al, 2020; Fujii et al, 2020; Hwang et al, 2020; Moskowitz et al, 2020; Sevransky et al, 2020; Vail et al, 2020).…”
Section: Resultsmentioning
confidence: 92%
“…3g) and compared ascorbic acid and thiamine with placebo in 111 patients, but did not find significant outcome differences (67). A further single center propensitymatched study observed a shorter duration of ventilation in adults with sepsis receiving HAT therapy compared to hydrocortisone alone (68). The VICTAS trial utilized an adaptive design and was terminated after recruitment of 501 participants as funding was withheld by the main founder, despite interim analyses not having reached neither futility nor superiority thresholds (69)(70)(71).…”
Section: Safety Of High-dose Ascorbic Acidmentioning
confidence: 99%
“…Questions about its reproducibility and generalizability require further investigation. Since then, a number of follow‐up trials using various study designs have been published and showed conflicting results 60–65 . For example, the VITAMIN Open‐Label Trial failed to demonstrate any survival benefits or reduced need for vasopressors 60 .…”
Section: Scientific Processmentioning
confidence: 99%
“…Since then, a number of follow-up trials using various study designs have been published and showed conflicting results. [60][61][62][63][64][65] For example, the VITAMIN Open-Label Trial failed to demonstrate any survival benefits or reduced need for vasopressors. 60 Currently, there are a number of ongoing clinical trials designed to further understand the impact of this intervention, the science in supporting the mechanism, the patient population most likely to receive the benefits, and the optimal regimens and methods to administer the regimens and monitor the clinical responses.…”
Section: When Premature Factulation Meets Binary Thinkingmentioning
confidence: 99%